Determination of Electrons Temperature and Density For Ag, Zn, and Cu metals using Plasma jet System at atmospheric pressure - Jihad, Ghaith H.; Aadim, Kadhim A. (Iraqi Journal of Science, 2022)
Under atmospheric pressure, an argon plasma stream was sustained and its plasma characteristics were examined. The emission spectra of plasma created in a plasma jet system using argon gas were observed for three metals (Ag, Zn, and Cu) for the anode and varied flow rates ranging from 1–4 L/min. at constant voltage, and normal atmospheric pressure. The spectral lines of excited Ar, Ag, Zn, and Cu species were identified at a wavelength of (650–900) nm .The Debye length, sphere, and temperature of an electron are all measured. Optical emission spectrometer (OES) equipment was used to capture the spectrum produced by the plasma at various argon gas flow rates.The temperature and density of the electron (Te) and (ne) ranges for Ar-gas, Ag, Zn, and Cu-anode increased as the stream pace of argon gas to the plasma made by the release current (D.C.) expanded.(1.241- 1.473)eV and (1.93 x1018–6.38 x1018 ) cm-3 , (1.187– 1.245) eV and  (4.32 x1016–6.23 x1016 ) cm-3 , (1.374 -1.631)eV and (4.01 x1018 – 12.1 x1018 ) cm-3 respectively . The intensity of spectral lines, on the other hand, increased.